Pemberdayaan Ibu-Ibu PKK melalui Inovasi Kerajinan Kreatif Berbasis Kain Perca - Nadhiroh, Azizatun; Dwi Andini, Sania; Vega Septiani, Wahyu Felisia; Cahya Utami, Lulu Alvina; Kuswardinah, Asih; Nurmasitah, Sita (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
This community service program aimed to enhance the skills of PKK women in RT 05 RW 05 Sekaran in turning textile waste, especially patchwork, into valuable handicraft products. Using the Community Development Practice method, the program emphasized community empowerment through educational workshops, hands-on training, mentoring, and participatory evaluation. The chosen product—patchwork folding fans—was selected for its simplicity and market potential. As a result, participants showed a notable increase in both knowledge and skills. They were actively involved in all stages of product creation, reflecting a growing interest in entrepreneurship and environmental responsibility. The program also fostered greater awareness of the importance of waste management as a shared duty. Overall, this initiative demonstrated how local, skill-based training can contribute to sustainable economic and environmental outcomes. Even on a small scale, such efforts in community empowerment can serve as practical steps in addressing larger social and ecological challenges.